2005
DOI: 10.1681/asn.2005030312
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Acute Rejection after Early Cyclosporine Withdrawal in Renal Transplant Recipients Who Receive Mycophenolate Mofetil

Abstract: The aim of this randomized, open-labeled trial was to compare the incidence of acute rejection after an early (3 mo posttransplantation) withdrawal of cyclosporine (CsA) or mycophenolate mofetil (MMF) in renal transplantation. Among 218 eligible recipients, 108 nonsensitized, rejection-free patients who were under a triple drug regimen (CsA-MMF-prednisone) and had received a first kidney from a deceased donor were enrolled. At 3 mo after graft, they were gradually withdrawn from CsA (MMF group, n ‫؍‬ 54) or MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…Accordingly, a 12-mo study of 77 patients found that when CsA was withdrawn at 3 mo from a triple-therapy regimen that comprised MMF ϩ steroids, a low mycophenolic acid AUC 0 to 12 at the time of CsA discontinuation was a predictor for later acute rejection (13). The hypothesis that therapeutic drug monitoring of MMF may be advantageous when CsA is withdrawn is also being investigated in an ongoing study by Dr. J. de Fijter in Leiden, Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a 12-mo study of 77 patients found that when CsA was withdrawn at 3 mo from a triple-therapy regimen that comprised MMF ϩ steroids, a low mycophenolic acid AUC 0 to 12 at the time of CsA discontinuation was a predictor for later acute rejection (13). The hypothesis that therapeutic drug monitoring of MMF may be advantageous when CsA is withdrawn is also being investigated in an ongoing study by Dr. J. de Fijter in Leiden, Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were switched from CsA to tacrolimus if they experienced a steroid-resistant acute rejection episode. The main results from this trial were as follows: (1) at 1 year, although graft function was better preserved in the MMF group, the risk of BPAR was 13% higher (it is noteworthy that patients experiencing BPAR after CsA withdrawal more frequently showed borderline changes at M3 and had a lower exposure to MMF) 9 ; the chronic allograft damage index was equivalent in the two groups 13 ; and the incidence of focal or diffuse C4d deposits was significantly higher in the MMF group; and (2) at 2 years, graft function remained better in the MMF group, but persistent CsA exposure was not an independent risk factor for a decline in graft function.…”
Section: Population Studymentioning
confidence: 96%
“…Because acute rejection is known to trigger the occurrence of EMT in grafts, 10 and because in this trial biopsy-proven acute rejection (BPAR) was more frequent in the MMF group, 9 we wanted to rule out a possible confusing effect of BPAR on the change in the EMT score. We therefore performed a subgroup analysis excluding BPAR episodes (i.e., after excluding two patients from the CsA group and eight patients from the MMF group).…”
Section: Change In Emt Scores From M3 To M12mentioning
confidence: 99%
See 2 more Smart Citations